XÁC ĐỊNH CÁC VỊ TRÍ THẤM, XÓI LỞ VAI CÔNG TRÌNH CỐNG THỦY LỢI BẰNG KẾT HỢP CÁC CÔNG NGHỆ ĐỊA VẬT LÝ NÔNG - Cánh, Trần; Bắc, Trịnh Việt; Phòng, Lại Hợp; Vũ, Trần Anh (Vietnam Journal of Earth Sciences, 2012)
Determination of the seepage and eroded locations on the sluices shoulders by combining the near surface geophysical technologiesThere are more than 2,800 sluices under the River dike system in Northern Vietnam, which supply water, flooding drainage for agriculture and water transport. In operation, the weak soil zone at the contacts between sluice walls and dike bodies (called sluice shoulder) often occurred. These zones can cause seepages and erodes at the sluice shoulder at flooding time and might lead to break of dikes. In the paper the authors propose a combination of four geophysical methods in order to investigate and determine the weak locations at sluice, that consist of electromagnetic method, resistivity tomography, low frequency induced polarization and shallow seismic.The investigating results at the sluice Nham Lang belong to the right dike of Luoc River in Hung Ha district, Thai Binh province demonstrate high efficiency of this combination as following: 1/ under sluice foundation in landsite existed an weak soil zone at depth from -2.3m to -15m. This zone was the cause of the sagging of sluice foundation; 2/ The anomaly locations at sluice shoulder in landsite have been estimated, which caused strong seepages and eroding at flooding time, when flooding water levels increase more than 2.5m height; 3/ The results have been given to administration of this hydraulic engineering for monitoring and repairing.